2021
DOI: 10.1016/j.tranon.2020.100925
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels correlate to the progression of gastric cancer with neuroendocrine immunophenotypes: A multicenter retrospective study

Abstract: Highlights The serum lipid patterns of GCNEI differed from those of pure gastric adenocarcinoma significantly. Serum lipid levels correlated to the progression of GCNEI. Serum lipid levels impacted the risk of the occurrence of GCNEI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Contrary to previous study [22,23], serum lipid level was not an independent prognostic predictor of survival outcome in PanNENs. There were multiple reasons that lead to this conclusion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous study [22,23], serum lipid level was not an independent prognostic predictor of survival outcome in PanNENs. There were multiple reasons that lead to this conclusion.…”
Section: Discussioncontrasting
confidence: 99%
“…Multicenter research has discovered that obviously lower HDL and TC existed in the gastric cancer with neuroendocrine immunophenotypes group in comparison to normal population. Higher TG and HDL may reduce overall risk of developing gastric cancer with neuroendocrine carcinoma [22]. In digestive NENs, the survival rate of patients with high LDL levels was 4.738 times higher than that of patients with low LDL levels (95% CI:1.424-15.772, P = 0.019), but there is not evidently relevance on survival time [23].…”
Section: Discussionmentioning
confidence: 94%
“…Two studies showed that a population exposed to a higher level of total cholesterol (TC) would signi cantly increase the risk of GC incidence (Lim et al 2022; Kitahara et al 2011). Following evidence con rmed these preceding ndings and further found elevated low-density lipoprotein cholesterol (LDL-C) (Pih et al 2021;Zou et al 2021) and triglyceride (TG) (Li et al 2018) may also increase the incidence risk of GC. Furthermore, high-density lipoprotein cholesterol (HDL-C) was traditionally believed to be a protective factor for cardiovascular diseases, whereafter several prospective studies have shown that lower HDL-C would also increase the risk of GC (Li et al 2018;Lim et al 2022;Nam et al 2019).…”
Section: Introductionmentioning
confidence: 84%
“…According to the data on preoperative HDL-C or LDL-C levels, patients were divided into HDL-low (< 1.15 mmol/L) and HDL-normal (≥ 1.15 mmol/L and < 1.68 mmol/L) groups (due to the low proportion of GC with elevated HDL-C [ 27 ], those patients were not included in this study) or LDL-low (< 2.10 mmol/L), LDL-normal (≥ 2.10 mmol/L and < 3.10 mmol/L) and LDL-high (≥ 3.10 mmol/L) groups.…”
Section: Methodsmentioning
confidence: 99%